2018
DOI: 10.1016/j.virol.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

A novel p53 paralogue mediates antioxidant defense of mosquito cells to survive dengue virus replication

Abstract: Mosquito cells allow dengue viruses (DENVs) to undergo replication without causing serious deleterious effects on the cells, leading to advantages for dissemination to other cells. Despite this, increased accumulation of reactive oxygen species (ROS) is usually detected in C6/36 cells with DENV2 infection as shown in mammalian cells. Uniquely, oxidative stress caused by the ROS is alleviated by eliciting antioxidant defense which leads to protection of mosquito cells from the infection. In the present study, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…These results and reports also suggested that HlPrx2 proteins have a low possibility of being related to LGTV replication in the BHK cells. Chen et al (2018) reported that DENV replicates and induces ROS production in a mosquito-derived cell line without a cytopathic effect (CPE), while the infection of a mammalian cell line leads to cell death. Likewise, although LGTV infection of BHK cells induced CPE in the cells at Day 3 after inoculation, LGTV could replicate in an I. scapularis tick cell line (ISE6) without inducing CPE in the cells (Mlera et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These results and reports also suggested that HlPrx2 proteins have a low possibility of being related to LGTV replication in the BHK cells. Chen et al (2018) reported that DENV replicates and induces ROS production in a mosquito-derived cell line without a cytopathic effect (CPE), while the infection of a mammalian cell line leads to cell death. Likewise, although LGTV infection of BHK cells induced CPE in the cells at Day 3 after inoculation, LGTV could replicate in an I. scapularis tick cell line (ISE6) without inducing CPE in the cells (Mlera et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…During dengue virus (DENV) infection, apoptosis is the usual outcome [ 60 ]. Apoptosis is usually brought about by the production of viral proteins, which disrupts the function of the endoplasmic reticulum (ER), resulting in the accumulation of misfolded and unfolded proteins.…”
Section: Vector Competency and Oxidative Stressmentioning
confidence: 99%
“…The p53 is a transcription factor that selectively transcribes the catalase gene, which alleviates ROS accumulation within the cells, therefore reducing the rate of apoptosis ( Figure 1 B). In experiments that reduced the expression of the p53 gene, ROS accumulated in the infected cells [ 60 ]. In Ae.…”
Section: Vector Competency and Oxidative Stressmentioning
confidence: 99%
“…The balance between a rapid apoptosis and a delayed, secondary necrosis may explain in part the differences between tolerant and resistant mosquitoes' strains. For more details see [177,[189][190][191][192][193][194][195][196] and Figure 3 for suggested mechanisms which may be involved in alphavirus infection in sensitive versus resistant mosquitoes, extrapolated from other arboviruses. In addition to the virus' ability to penetrate the cells of a particular mosquito (specific receptor, lipid membrane composition), the difference between resistant and tolerant strains may also lie in the rapidity of cell response to viral infection in the first targeted tissue, i.e., the mosquito gut.…”
Section: Interplay Between Cell Death and Susceptibility Of Mosquito mentioning
confidence: 99%
“…Sensitive mosquitoes may tolerate viral infection through IAP-dependent apoptosis inhibition, as shown for the arbovirus bluetongue virus (BTV) [191,192]. Another tolerance mechanism to DENV seems to rely on resistance to oxidative stress through CAT protection in mosquito gut [193] or p53 isoforms regulation leading to cell survival in drosophila [194] and mosquito [195,196]. Delayed apoptosis may then lead to secondary necrosis, impairing a proper innate immune response, favoring basal lamina damage and viral spread [189].…”
Section: Interplay Between Cell Death and Susceptibility Of Mosquito mentioning
confidence: 99%